90 songs for voice and piano (Low) - SCHUMANN (international Music Co., 1954)
Liederkreis Op. 39nFrauen liebe und leben Op. 42nDichterliebe Op. 48n54 Selected songsn4 mignon's songs from goethe's Wilhelm meister""